PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA UMKM SERABI - Yanti S.SE,MM; Riscki Elita Rosihana; Muhammad Khoiruddin Harahap (Jurnal Manajemen Dan Akuntansi Medan, 2025)
To determine a company's success in generating profits, one can look at the company's ability to use working capital productively. Therefore, it is necessary to use profitability ratios to determine the extent of a company's ability to generate profits for its owners through all of its capabilities and resources. This study aims to determine whether there is an influence between working capital and profitability in Serabi MSMEs. The data source used in this study is primary data obtained from the field in the form of observation results. The data collection method was carried out through participatory and covert observation, which involved directly observing the object and participating in daily activities. The data was sourced from the financial reports of Serabi SMEs from March to June 2023. The data was analyzed using profitability ratios such as net profit margin (NPM), gross profit margin (GPM), and return on assets (ROA), yielding percentage levels that indicate the company's effectiveness in managing working capital. The results of this study are as follows: A. There is a relationship between working capital and profitability, meaning that the larger the working capital, the greater the profit obtained. B. Serabi SMEs are not yet efficient in managing their working capital, as evidenced by the NPM calculation, which is still below 5%, so it cannot be considered good. C. Serabi SMEs are capable of generating good gross profit, with the GPM ratio percentage nearly reaching 5%, and the company can be considered satisfactory. D. Serabi SMEs are productive in generating net profit, as evidenced by the ROA percentage exceeding 5%, so the company can be considered good.